2007
DOI: 10.1007/s11239-007-0037-5
|View full text |Cite
|
Sign up to set email alerts
|

Inferior vena caval tumor thrombus extending into the right atrium in a patient with pancreatic cancer

Abstract: Venous thromboembolism is a common complication in patients with cancer and an important cause of morbidity and mortality. Idiopathic thrombosis, migratory or recurrent thrombophlebitis may be the first manifestation of an occult malignancy. While deep venous thrombosis and pulmonary embolism are the most common thrombotic conditions in patients with malignant disease, tumor thrombus may be seen in inferior vena cava, mainly in patients with renal cell carcinoma, hepatocellular carcinoma, testicular tumors or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Presentation of a tumor thrombus is non-specific and typically by time of presentation prognosis is poor [ 6 ]. Thus, treatment is complex and frequently doesn't affect overall outcome [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Presentation of a tumor thrombus is non-specific and typically by time of presentation prognosis is poor [ 6 ]. Thus, treatment is complex and frequently doesn't affect overall outcome [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scattered case reports of ovarian haemangioma (Tamburino et al, 1992), testicular tumour (Kanda et al, 1991), embrional carcinoma of the testis (Paule et al, 1991), testicular teratoma (Moon et al, 1992) and even pancreatic cancer (Ozben et al, 2007) have been reported so far.…”
Section: Othersmentioning
confidence: 99%
“…Scattered case reports of ovarian haemangioma (Tamburino et al, 1992), testicular tumour (Kanda et al, 1991), embrional carcinoma of the testis (Paule et al, 1991), testicular teratoma (Moon et al, 1992) and even pancreatic cancer (Ozben et al, 2007) have been reported so far.…”
Section: Othersmentioning
confidence: 99%